2018
DOI: 10.21474/ijar01/7245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heartfulness Self Development Program on Psychological Flourishing of Student Nurses.

Abstract: Nursing students, Psychological flourishing, Heartfulness selfdevelopment program. Objective: To evaluate the effects of Heartfulness self-development program in improving psychological flourishing of nursing students. Methodology: The study was designed as a prospective interventional study to examine the effects on positive psychological flourishing parameters such as empathy, optimism, self-confidence, positive outlook towards future, and social responsibilities. Participants of this study are students of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…16,17 All of the physiological parameters such as pulse rate, blood pressure, and heart rate variability were perfectly controlled in the long-term practitioners. 18 Heartfulness meditation increases calmness and increases tolerance to anger and stress. 19 Another study reported that the autonomic parameters were well controlled followed by the meditation.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 All of the physiological parameters such as pulse rate, blood pressure, and heart rate variability were perfectly controlled in the long-term practitioners. 18 Heartfulness meditation increases calmness and increases tolerance to anger and stress. 19 Another study reported that the autonomic parameters were well controlled followed by the meditation.…”
Section: Discussionmentioning
confidence: 99%